Efficacy of aerosol applications of methoprene and synergized pyrethrin against Tribolium castaneum adults and eggs - Tucker, Angela M.; Campbell, James F.; Arthur, Frank H.; Zhu, Kun Yan (My University, 2014)
Experiments were performed to determine the efficacy of a single aerosol application of the insecticides methoprene and piperonyl butoxide-synergized pyrethrin, alone or in combination, and the insecticide carrier, Isopar M, against Tribolium castaneum (Herbst), the red flour beetle. The initial test exposed adults to insecticide treatments and placed male/female pairs in flour. All adults exposed to synergized pyrethrin were knocked down for at least 24 h after exposure but they recovered. High adult survival and similar average numbers of living F1 progeny were produced regardless of treatment exposure. In a separate test, insecticide treatments were directly applied to newly laid eggs, which resulted in the suppression of egg hatch. Synergized pyrethrin was the most effective insecticide (P ≤ 0.001) for suppressing egg hatch. The effect of flour on insecticide activity to eggs and consequent insect development was also evaluated. An amount of 0.01 g of flour in the exposure arena, 62-cm2 area, was not sufficient for individuals to develop beyond the early larval stages, regardless of the treatment. As the flour amount in the arena increased from 1 to 5 g, the number of eggs that could develop to the adult stage increased, but this number was significantly lower in the insecticide treatments than in the control or carrier treatments. The results of the later tests indicate a high efficacy of the insecticides alone or in combination on T. castaneum egg hatch and development to the adult stage.
Citation: Tucker, Angela M., James F. Campbell, Frank H. Arthur, and Kun Yan Zhu. 2014. “Efficacy of Aerosol Applications of Methoprene and Synergized Pyrethrin Against Tribolium Castaneum Adults and Eggs.” Journal of Economic Entomology 107 (3): 1284–91. https://doi.org/10.1603/EC13507.
Keywords: Tribolium castaneum; Methoprene; Synergized pyrethrin; Efficacy; Aerosol application